Viscous Flow Approach to Rapid Infiltration and Drainage in a Weighing Lysimeter - Germann, P.F. (2020)
Rapid infiltration and drainage in a free‐draining weighing lysimeter are assessed with a viscous flow approach that is based on the concept of moving water films. The two parameters film thickness and specific contact area of the film per unit volume of the permeable medium together with the rate and duration of water input suffice to quantify viscous flow at the Darcy scale. The two parameters are deducible from wetting front velocities and water content variations during the passing of the film. Temporarily perching water tables at lysimeter bottoms are considered artifacts of the lysimeter method that may severely alter the biogeochemistry of the effluent. The viscous flow approach assesses the duration of water perching from drainage flow interpretation. Perching in the sense of viscous flow occurred at most 10% of the time during drainage flow. Drainage ceased completely during a 6‐mo period that yielded only 46% of rainfall compared with the 30‐yr average. During rewetting of the lysimeter soil, viscous flow applied to infiltrations of nine precipitation episodes, showing successive penetrations of wetting fronts shortly before the onset of drainage.